A low-cost demonstration kit for locating an image formed by a plane mirror integrated with a ray diagram - Kreetha Kaewkhong (2018)
© 2015 IOP Publishing Ltd. This article introduces a low-cost, easy to make apparatus that can be used to locate the position of an image formed by a plane mirror. The apparatus is combined with a method used to identify an image's position by drawing a ray diagram, based on the principle of reflection, to show how an image is formed. An image's distance and an object's distance can be measured precisely. In addition, the size of an object and an image can be determined accurately.